2005
DOI: 10.1007/s00436-005-1313-y
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses during pregnancy in heifers naturally infected with Neospora caninum with and without immunization

Abstract: This study was designed to identify changes in parasite-specific immune responses that occur during vertical transmission of Neospora caninum and can be used as indicators of parasite reactivation in naturally infected heifers. Ten heifers were unimmunized and 11 immunized with killed tachyzoites. One unimmunized heifer, which aborted at week 19 of gestation, had an increase in parasite-specific antibodies, mainly IgG(2), from week 15 to week 19 and a concomitant decline in parasite-specific cell-mediated immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 30 publications
2
21
0
14
Order By: Relevance
“…However, at present, protection from endogenous transplacental transmission in controlled cattle has not been shown for any vaccine. When pregnant heifers naturally infected with N. caninum were immunized with killed tachyzoites or left untreated, the results suggested that reactivation of a latent infection had occurred in the naturally infected heifers, regardless of their immunization status, and that immunization with the POLYGEN-adjuvanted, killed N. caninum tachyzoite preparation had not been not able to prevent vertical transmission in naturally infected heifers (17).…”
Section: Control Measuresmentioning
confidence: 99%
“…However, at present, protection from endogenous transplacental transmission in controlled cattle has not been shown for any vaccine. When pregnant heifers naturally infected with N. caninum were immunized with killed tachyzoites or left untreated, the results suggested that reactivation of a latent infection had occurred in the naturally infected heifers, regardless of their immunization status, and that immunization with the POLYGEN-adjuvanted, killed N. caninum tachyzoite preparation had not been not able to prevent vertical transmission in naturally infected heifers (17).…”
Section: Control Measuresmentioning
confidence: 99%
“…This suggests that a population of memory T cells was present in these animals. Others have previously shown that proliferative responses in N. caninum-infected cattle are associated with CD4 ϩ T cells and that these are the principal secretors of IFN-␥ (1,16,29). In contrast, although the two lysate-immunized groups developed IFN-␥ and proliferation responses immediately following immunization, either no memory cells were induced or the precursor frequency of antigen-specific T cells was too low to produce enough IFN-␥ to be detected in our assays in these animals on the day of challenge, 15 weeks after the second immunization.…”
Section: Fig 2 Mean Gamma Interferon Responses (Ng MLmentioning
confidence: 99%
“…al. 2003;Andrianarivo et al 2005). However, other authors documented a lack of differences in the antibodies levels during the whole period of pregnancy (Fioretti et al 2000;Häsler et al 2006).…”
Section: Discussionmentioning
confidence: 99%